The Impact of Past and Current Alcohol Consumption Patterns on Progression of Carotid Intima‐Media Thickness Among Women and Men Living with HIV Infection. (28th February 2019) - Chichetto, Natalie E.; Plankey, Michael W.; Abraham, Alison G.; Sheps, David S.; Ennis, Nicole; Chen, Xinguang; Weber, Kathleen M.; Shoptaw, Steven; Kaplan, Robert C.; Post, Wendy S.; Cook, Robert L.
Abstract : Background: The relationship between alcohol consumption and atherosclerosis has not been sufficiently examined among people living with HIV (PLWH). Methods: We analyzed data from PLWH in the Women's Interagency HIV Study (WIHS; n  = 1, 164) and the Multicenter AIDS Cohort Study (MACS; n  = 387) with no history of cardiovascular disease (CVD). Repeated measures of intima‐media thickness of the right common carotid artery (CCA‐IMT) were assessed using B‐mode ultrasound from 2004 to 2013. Current alcohol consumption was collected at time of CCA‐IMT measurement and was categorized according to gender‐specific weekly limits. Group‐based trajectory models categorized participants into past 10‐year consumption patterns (1994 to 2004). Multivariate generalized estimating equations were conducted to assess the association of past and current alcohol use patterns on change in CCA‐IMT by cohort, controlling for age, race, cigarette and illicit drug use, probable depression, HIV RNA viral load, antiretroviral therapy exposure, and hepatitis C coinfection. Results: Among the WIHS, past heavy alcohol consumption was associated with increased CCA‐IMT level over time (β = 8.08, CI 0.35, 15.8, p  = 0.04), compared to abstinence. Among the MACS, compared to abstinence, all past consumption patterns were associated with increased CCA‐IMT over time (past low: β = 15.3, 95% CI 6.46, 24.2, p  < 0.001; past moderate: β = 14.3, CI 1.36, 27.2, p  = 0.03; past heavy: β = 21.8, CI 4.63, 38.9, p  = 0.01). Current heavy consumption was associated with decreased CCA‐IMT among the WIHS (β = −11.4, 95% CI −20.2, −2.63, p  = 0.01) and MACS (β = −15.4, 95% CI −30.7, −0.13, p  = 0.04). No statistically significant time by consumption pattern effects were found. Conclusions: In both cohorts, 10‐year heavy consumption was associated with statistically significant increases in carotid artery thickness, compared to abstinence. Long‐term patterns of drinking at any level above abstinence were particularly significant for increases in IMT among men, with heavy consumption presenting with the greatest increase. Our results suggest a potentially different window of risk among past and current heavy drinkers. Further studies are needed to determine whether alcohol consumption level is associated with intermediate measures of atherosclerosis. Alcohol screening and interventions to reduce heavy consumption may benefit PLWH who are at risk of CVD. Abstract : The relationship between alcohol consumption and atherosclerosis has not been sufficiently examined among people living with HIV (PLWH). We analyzed data from PLWH with no history of cardiovascular disease (CVD) using repeated measures of intima‐media thickness and alcohol consumption. Our results suggest a potentially different window of risk among past and current heavy drinkers. Alcohol screening and interventions to reduce heavy consumption may benefit PLWH who are at risk for CVD.